2002
DOI: 10.1108/02651330210425006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring channel internalization among Spanish exporters

Abstract: The internalizing of export operations inside the firm is examined with data from 2,264 Spanish exporters. An interpretive framework for understanding the channel integration decision is designed and tested. Results confirm that a higher proportion of firms decide to externalize their export marketing activities in the marketplace versus keeping them inside the firm. Additionally, some hypotheses related to the selection of the optimal level of channel integration in the international arena are also empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
3
39
0
2
Order By: Relevance
“…This kind of knowledge facilitates the firm's access and proper function in foreign markets through the choice of an appropriate distribution channel (Piercy, Katsikeas, & Cravens, 1997). Initially, the firm may choose distributors to gain access to the requisite market knowledge, but as the level of information steadily increases so does the need to exchange knowledge and cooperate with the distributor (Rialp, Axinn, & Thach, 2002). Lastly, given export market competitiveness, supporting the distributor is imperative to ensure adequate handling, effective promotion, timely delivery, and proper marketing for the product (O'Cass & Julian, 2003).…”
Section: Export Competitive Advantagementioning
confidence: 99%
“…This kind of knowledge facilitates the firm's access and proper function in foreign markets through the choice of an appropriate distribution channel (Piercy, Katsikeas, & Cravens, 1997). Initially, the firm may choose distributors to gain access to the requisite market knowledge, but as the level of information steadily increases so does the need to exchange knowledge and cooperate with the distributor (Rialp, Axinn, & Thach, 2002). Lastly, given export market competitiveness, supporting the distributor is imperative to ensure adequate handling, effective promotion, timely delivery, and proper marketing for the product (O'Cass & Julian, 2003).…”
Section: Export Competitive Advantagementioning
confidence: 99%
“…In keeping with this, a large part of the empirical research has observed that firm size is positively associated with the degree of commitment assumed with the entry mode Fast Track online article: unedited manuscript accepted by Tourism Economics (Agarwal and Ramaswami, 1992;Campa and Guillén, 1999;Driha and Ramón (2011);Osborne, 1996;Pla-Barbe et al, 2010;Ramón, 2002;Rialp et al, 2002;Stopford and Wells, 1972;Trevino and Grosse, 2002;Yu, 1990). This is why we can argue that larger-sized hotel firms will have better guarantees to assume the commitment derived from an FDI initiative, which leads us to expect that equity entry modes will be positively associated with firm size.…”
Section: Firm-specific Factors and Entry Mode Choicementioning
confidence: 92%
“…The research of Kim, Nugent, and Yhee (1997) and Osborne (1996) contributes to the literature on small-to medium-sized firms. Interest in smaller, younger, more entrepreneurial international firms seems to be generating increased attention (e.g, Chen and Huang 2004, McNaughton 2002, McNaughton and Bell 2000, Rialp, Axinn, and Thach 2002. A glance through the list of authors in Table 1 reveals that quite a few scholars have a growing body of work in this field.…”
Section: Structuralist Framework Research Methodsmentioning
confidence: 99%
“…A firm's optimal channel structure should reflect both the volume of sales involved and the vulnerability of the firm to opportunistic behaviors by external intermediaries (Klein 1991;Klein, Frazier, and Roth 1990;Klein andRoth 1990, 1993). Rialp, Axinn, and Thach (2002) examine the channel integration decision of over 2,000 Spanish firms engaged in exporting. They find strong evidence of internalizing operations.…”
Section: Transaction Cost Approachmentioning
confidence: 99%